Failed States and Fragile Societies A New World Disorder? - Miner, Steven M.; Trauschweizer, Ingo (Ohio University Press, 2014)
Since the end of the Cold War, a new dynamic has arisen within the international system, one that does not conform to established notions of the state's monopoly on war. In this changing environment, the global community must decide how to respond to the challenges posed to the state by military threats, political and economic decline, and social fragmentation. This insightful work considers the phenomenon of state failure and asks how the international community might better detect signs of state decay at an early stage and devise legally and politically legitimate responses.This collection of essays brings military and social historians into conversation with political and social scientists and former military officers. In case studies from the former Yugoslavia, Somalia, Iraq, and Colombia, the distinguished contributors argue that early intervention to stabilize social, economic, and political systems offers the greatest promise, whereas military intervention at a later stage is both costlier and less likely to succeed.Contributors: David Carment, Yiagadeesen Samy, David Curp, Jonathan House, James Carter, Vanda Felbab-Brown, Robert Rotberg, and Ken Menkhaus.